Penerapan Model Pembelajaran Mind Mapping Untuk Meningkatkan Motivasi Belajar IPS Siswa Kelas VIII MTS Miftahul Huda Ngeni Wonotirto Blitar - Muhamad Novi Aminudin; Binti Maunah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to increase students' social studies learning motivation through the application of the mind mapping learning model, this is due to the low level of students' learning motivation towards social studies subjects at MTs Miftahul Huda Ngeni Wonotirto Blitar. This study uses a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. The results of this research are (1) The steps for implementing the mind mapping learning model begin with determining the objectives to be achieved in learning, determining the material that will be presented in the mind map. After the material is determined, the next step is to prepare supporting tools. The next step is the learning process using the mind mapping learning model. (2) Student responses to the application of the mind mapping learning model get a good response from students. Students are more enthusiastic when learning activities use the mind mapping learning model. (3) The implications of applying the mind mapping learning model are a) students are interested in paying attention to the material presented, b) students become easier to understand the material, c) students become more enthusiastic about learning than usual, d) students become more active in learning activities using mind mapping model, e) student learning motivation has increased, besides that it will affect student learning outcomes.